PRINSIP KEADILAN HUKUM WARIS ISLAM TENTANG PEMBAGIAN WARISAN ANTARA LAKI-LAKI DAN PEREMPUAN - Siregar, Dahris (AS-SALAM, 2024)
Islamic law divides male and female heirs in a ratio of 2:1. The author wants to learn more about the division of inheritance influenced by men and women as heirs, as well as the interpretation of the division of inheritance in accordance with Islamic law. This study's goal is to promote a feeling of fairness. to all heirs by explaining the actual division of inheritance according to Islamic rules in society, and then to find out how inheritance is divided between each heir. This type of literature research studies documents by utilizing various secondary data sources, such as laws, court rulings, legal theories, and perhaps the views of academics who deal with the problem. Secondary data comes from books, journals, and other writings in line with the study's subject. Next, the data is evaluated using descriptive analytical techniques. The results showed that society first used the Islamic rule of partial inheritance division, dividing property according to the sex of heirs, with a ratio of 2:1 between men and women. Second, justice can be applied effectively as one of the pillars of community development and reduce conflicts between fellow heirs. However, the public does not understand the principles of Islamic inheritance and its laws.